Missed Diagnosis of Cesarean Scar Pregnancy: A Growing Reality - Dhar, Rinku Sengupta; Bhargava, Vijaylaxmi (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i1.5062 NJOG 2010 Jul-Aug; 5(1): 49-52